The Effect Of Customer Experience And Trust On Customer Loyalty At Seblak RC Karawang - Cindy Dwi Aprillia; Suroso Suroso; Dexi Triadinda (Journal of Applied Management and Business, 2026)
Aims - The primary objective of this research is to investigate and analyse the influence of customer experience and customer trust on customer loyalty at Seblak RC Karawang. The study seeks to determine whether these factors act independently or synergistically in fostering long-term consumer commitment within the competitive Indonesian street food sector. Methodology - This study employs a quantitative research design with a descriptive and causal explanatory approach. Data were gathered from 96 respondents via purposive sampling, specifically targeting dine in customers. The instruments were validated using r-table comparisons and Cronbach’s Alpha. Data analysis was conducted using IBM SPSS Statistics, encompassing classical assumption tests, multiple linear regression, and hypothesis testing (t-tests and F-tests). Findings - The results reveal a compelling statistical anomaly; partially, neither customer experience nor customer trust has a significant impact on loyalty (Sig. > 0.05). However, simultaneous testing (F-test) demonstrates a significant collective influence (Sig. 0.000), with a high Coefficient of Determination (R2) of 86.1%. This indicates that loyalty is not built on isolated factors but on the holistic integration of physical interaction and brand integrity. Research Limitations - The research is limited by its focus on a single geographic location and dine-in consumers. Practically, it implies that MSME owners must manage marketing strategies holistically rather than in fragments to ensure customer retention. Originality - This study offers unique insights into the complementary absolute nature of loyalty in the buffet style street food industry, where individual marketing pillars fail unless they are synchronised as a unified value proposition.